Bid-Ask Spreads with Indirect Competition Among Specialists - Thomas Gehrig; Matthew Jackson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1994)
Research Joint Ventures and subsidies are important R&D policy instruments. The regulator, however, is unlikely to know all the relevant information to regulate R&D optimally. The extent to which there are appropriability problems is one such variable that is private information to the firms within the industry. In a duopoly setting we analyze the characteristics of a first-best and second-best R&D policy where the government can either allow Research Joint Ventures or not and give lump-sum subisides to the parties involved. The second-best R&D policy improves upon the policy of an unsophisicated government by integrating reports of the firms on their spillovers and the correlation between the R&D spillovers of the firms into its formulation.
Keywords: 330